Study of springback behavior on u-bending part using die shoulder patterning method (DSPM) - Nurul Jannah, Baharuddin; Ahmad Rosli, Abdul Manaf; Ahmad Shahir, Jamaludin (2021)
U-bending is increasingly used in the sheet metal industry for the manufacturing of car door pillars and beams. However, the springback phenomenon that occurs after removing the sheet metal from the fixtures leads to altered product accuracy, rejection, and increased manufacturing costs. Thus, minimizing springback in the bending of sheet metal is vital to maintain close geometric tolerances in the deformed parts of the metal. Many studies have been performed on the prediction of springback occurrence based on various experiments and simulations. Nevertheless, no study has been performed to reduce springback occurrence, especially during the hat-shaped fabrication process. In this study, the hat-shaped part is deformed using the die shoulder patterning method (DSPM) and validated using three-way ANOVA. It was shown that all the DSPM models improved the accuracy of the deformed parts by exhibiting greater contact area during the bending process, thus reducing the springback of the deformed parts. The DSPM with a radius of 5 mm and rib size of 0.4 mm successfully minimized springback as the contact area and sliding stress between the die shoulder and surface of the blank were optimized for AISI 1030.